Marriage registration procedures and its legal impacts - Mariadi Mariadi (Tunas Institute, 2023)
This article aims to review the procedures for registering marriages and the legal impacts of registering marriages, as well as the negative impacts arising from marriages that are not registered. Marriage registration is one of the essential requirements for the validity of a marriage; this is because a registered marriage can provide legal certainty to the parties involved in the marriage, including husband, wife and children, regarding the rights arising from the marriage, such as inheritance rights. , the right to obtain a birth certificate, the right to a living wage, and so on cannot be obtained if the marriage is not registered/not legal. Marriages that are not registered (nikah sirri) are not valid according to state law and harm the status of children. The status of children born through unregistered marriages is illegitimate in state administration, so they will have difficulty obtaining marriage rights.